Book Reviews (Rev. Anal. Numér. Théor. Approx., 2011)
Book reviews for:Leah  Edelstein-Keshet, Mathematical Models in Biology, Society for Industrial and Applied Mathematics, Philadelphia, USA, 2005, ISBN: 978-0-89-871-554-5, XXXI+586 pp. Reviewed by D. Otrocol.Wim Michiels and Silviu-Iulian Niculescu, Stability and Stabilization of Time-Delay Systems:  an Eigenvalue-Based Approach, Society for Industrial and Applied Mathematics, Philadelphia, USA, 2007, ISBN: 978-0-898716-32-0, XXI+378 pp. Reviewed by D. Otrocol.Germund Dahlquist and Ake Bjorck, Numerical Methods in Scientific Computing, Volume I, Society for Industrial and Applied Mathematics, Philadelphia, USA, 2008, ISBN: 978-0-898716-44-3, XXVII+717 pp. Reviewed by D. Otrocol.